Manajemen Strategi Pengelolaan Perpustakaan Desa sebagai Pusat Sumber Belajar Masyarakat di Desa Montong Beter: Strategic Management of Village Library Management as a Community Learning Resource Center in Montong Beter Village - Ahmad Izzudin; Kamaruddin; Lalu Helmi Yusup; Lalu Wiranda Jayadi; Losi Wasdani (Al-Gafari : Manajemen dan Pendidikan, 2026)
The existence of a village library plays a very important role for the community, because with the existence of a library it can support the community in obtaining information and increase the existence of the village in introducing the existence and progress of the village. The purpose of this study is to determine the role of the library as a center for community learning resources and to determine strategic management in managing the Montong Beter village library. This type of research is qualitative research. Data collection techniques through observation, interviews, documentation. Data analysis techniques use descriptive analysis. The results of this study indicate that the library has a very important role as a center for community learning resources. The strategic management in managing the Montong Beter village library is carried out in various ways including involving the community in various activities related to the library, holding mobile libraries to educational institutions and integrated health posts (posyandu) and collaborating with various parties as a partnership.